CHEMICAL AND MINERALOGICAL CHARACTERIZATION OF GIDAN JAJA IRON ORE, ZAMFARA STATE, NIGERIA (Nigerian Journal of Technology, 2018)
The chemical and mineralogical characteristics of Gidan Jaja iron ore located in Zurmi Local Governmental Area of Zamfara State was carried out using X-ray Fluorescence (XRF) spectrometer, X-ray Diffractometer (XRD), Scanning Electron Microscope (SEM) and Optical Microscope. The XRF results obtained revealed that Gidan Jaja Iron ore has an average content of 73.79 % Fe2O3, 0.52 % MnO, 17.50 % TiO2, 0.11 % CaO, 0.50 % Cr2O3, 3.84 % SiO2, 0.43 % Al2O3, 0.034 % CuO, 0.02 % NiO, 0.46 % PbO, 2.76 % LOI. Phosphorus and Sulphur were below limit of detection. XRD analysis revealed that the ore contained 56 % Ilmenite, 34 % Magnetite and 10 % Spinel minerals. Petrographic study using polarized light revealed that the iron bearing minerals are predominantly Ilmenite and Magnetite, with minor amount of hematite, spinel and quartz. The results obtained from SEM analysis showed that the iron bearing minerals are separated from other minerals in the ore by smooth grain boundaries. The quality of the ore was compared with ores from other part of Nigeria, and based on the results obtained in this research work, Gidan Jaja iron ore can be classified as high grade, low silica, ilmenite iron ore. Finally combined results from chemical and mineralogical characterization of the iron ore deposit indicated that, the iron ore can be a source of iron ore for use in iron production. Key words: Chemical, Mineralogical, Characterization, Gidan Jaja, Iron ore http://dx.doi.org/10.4314/njt.v38i1.12